Design and analysis of urban concept car chassis for shell eco-marathon challenge - Muhamad Solehin, Daud (2012)
The Shell Eco - marathon is an educational project that challenges competing student teams to design, build and drive the most energy-efficient vehicle. The winning vehicle is the one that travels the furthest using the least amount of fuel. Contestants at the Shell Eco-marathon find increasingly innovative ways to squeeze more out of a litter of energy. They can make it last for the equivalent of several thousand kilometers. The Shell Eco-marathon aims to inspire engineering students to develop new approaches to sustainable mobility and fuel efficiency. One of the main points to achieve fuel consumption is by reducing the weight of the car chassis. In this study student will design a new chassis for UMP team who participated in SEM challenge. The designed chassis then will be analyzed with required load and will select the best chassis from the parameters. The selected chassis will be proposed to the UMP team to be used as the next urban concept car chassis.